Serum uric acid and nonalcoholic fatty liver disease - Fan, Jia; Wang, Dongxu (Frontiers in Endocrinology, 2024)
Nonalcoholic fatty liver disease (NAFLD) is characterized by over 5% hepatic fat accumulation without secondary causes. The prevalence of NAFLD has escalated in recent years due to shifts in dietary patterns and socioeconomic status, making it the most prevalent chronic liver disease and a significant public health concern globally. Serum uric acid (SUA) serves as the end product of purine metabolism in the body and is intricately linked to metabolic syndrome. Elevated SUA levels have been identified as an independent risk factor for the incidence and progression of NAFLD.. This paper reviews the relationship between SUA and NAFLD, the underlying mechanisms of SUA involved in NAFLD, and the potential benefits of SUA-lowering therapy in treating NAFLD. The aim is to raise awareness of SUA management in patients with NAFLD, and to encourage further investigation into pharmacological interventions in this area.